2020
DOI: 10.1080/10643389.2020.1860406
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles and their application to ozonation in water treatment: A critical review exploring their benefit and future application

Abstract: Ozonation is a widely applied water treatment process, used for oxidation of contaminants, as well as for the disinfection of water. However, the conventional ozonation process demands a high energy requirement and deep tanks to ensure effective mass transfer and oxidation.Microbubble technologies have emerged which have the potential to improve gas-liquid contacting. Microbubbles have diameters of 1-100 µm, while conventional bubbles used in ozonation are between 2 -6 mm. Microbubbles have many favorable char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 145 publications
(205 reference statements)
0
16
0
Order By: Relevance
“…Previous research has shown that the use of microbubbles in place of conventionally produced fine bubbles can enhance mass transfer [25], increase gas utilisation efficiency [38] and increase the rate and extent of compound removal [2] during ozonation. As such, they are now being considered to replace conventional bubble (2 -6 mm) systems [9].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has shown that the use of microbubbles in place of conventionally produced fine bubbles can enhance mass transfer [25], increase gas utilisation efficiency [38] and increase the rate and extent of compound removal [2] during ozonation. As such, they are now being considered to replace conventional bubble (2 -6 mm) systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…This size difference results in a significantly higher interfacial area [22] and a decrease in rise velocity leading to an extended contact time for the microbubble systems compared to conventional systems [24]. These features allow for a faster and more extensive transfer of gas into the liquid phase [27] which can lead to enhanced treatment [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations